Case study on the growth and ecosystem of Vietnamese data journalism - Tri, Nguyen Minh (Universitas Padjadjaran, 2026)
Background: Data-driven journalism (DDJ) has become a significant part of today’s news landscape, though its growth varies widely around the world. Most research has focused on Western countries, leaving us with a limited understanding of places like Vietnam. In Vietnam, state control and limited press freedom sit alongside stricter digital policies and more competitive markets, creating unique ways for DDJ to develop. Purpose: This study explores how data-driven journalism started and grew in Vietnam, highlighting what makes it special, the challenges it faces, and where it might head in the future. Methods: The study adopts a friendly, inclusive approach using a mixed-methods framework. It thoughtfully combines a systematic review of academic literature spanning 2003 to 2025 with a qualitative analysis of national digital transformation and media policy documents. Additionally, it features engaging case studies of well-known Vietnamese news organizations, offering comprehensive, relatable insight into the topic. Results: While laws support openness, accessing public data in Vietnam remains challenging. Digital journalism tends to focus more on storytelling with images rather than heavy data. However, positive steps are underway. Still, many reporters aren’t familiar with coding, and oversight rules can make their work more difficult. We’re seeing progress and hope for more improvements soon. Conclusion: The study shows that DDJ has become an important part of digital journalism in Vietnam. However, it still faces some limitations due to existing rules and institutions. Implications: This study enriches DDJ scholarship by moving beyond Western-centric methods and underscores the need for improved access to data. It also discusses the importance of professionals continuing to learn and the changing economics of digital media. The rise of Generative AI brings new problems that need flexible solutions.